In Search of the Factors Behind Naive Sentence Judgments: A State Trace Analysis of Grammaticality and Acceptability Ratings - Langsford, Steven; Stephens, Rachel G.; Dunn, John C.; Lewis, Richard L. (Frontiers in Psychology, 2019)
We present a state-trace analysis of sentence ratings elicited by asking participants to evaluate the overall acceptability of a sentence and those elicited by asking participants to focus on structural well-formedness only. Appealing to literature on `grammatical illusion' sentences, we anticipated that a simple instruction manipulation might prompt people to apply different weights to different aspects of acceptability in the two conditions. The state trace analysis of the rating data indicates that some dissociations between subjective judgments of acceptability and grammaticality are consistent with both judgment types accessing a single underlying factor. These results add to the existing comparisons between analytic and probabilistic modeling approaches to predicting rating judgments.